Assessing Service Quality and Tourist Satisfaction in Community-based Tourism: The Case of Mountainous Areas, Hue City, Vietnam - Hiep, Nguyen Le; Minh, Dao Duy; Thuy, Bui Thi; Quang, Le Ngoc Luu (International Review of Management and Marketing, 2026)
This study aims to evaluate the satisfaction of domestic tourists with the quality of community-based tourism (CBT) services in, mountainous areas, Hue city—a locality with a 20-year history of developing this type of tourism. Besides promoting tourism-driven economic growth, CBT activities here also contribute significantly to preserving and enhancing the cultural and historical values of the Co Tu community. Based on a survey of 150 tourists, the study employs exploratory factor analysis (EFA) and correlation regression methods to identify factors affecting tourist satisfaction. The regression analysis results reveal six positive factors influencing tourist satisfaction, including service capacity, reliability, empathy, responsiveness, perceived pricing, and tangible facilities. Among these, "service capacity" has the strongest impact, while "tangible facilities" exert the weakest influence. The research model achieves a high explanatory power, with an adjusted R² coefficient of 0.823 (82.3%). Based on these findings, the study proposes several solutions aimed at improving the identified factors, enhancing service quality, and increasing tourist satisfaction to support the sustainable development of community-based tourism in the area.